The Influence of Revenue and Operational Costs on Income tax in Food and Beverage Sub-Sector Companies - Tri Pratiwi, Endang; Amiruddin, Amiruddin; Alam, Syamsu (Dinasti Publisher, 2025)
This study aims to determine the effect of revenue and operational costs on income tax in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). This study uses secondary data in the form of financial statements for the 2018-2023 period obtained through the official website of the Indonesia Stock Exchange. The sample was determined through a purposive sampling technique with the number of samples that met the criteria as many as 16 companies. Data analysis uses multiple linear regression analysis. The results of the study show that partially revenue affects income tax in a positive direction and operational costs affect income tax in a positive direction. Meanwhile, simultaneously revenue and operational costs affect income tax. This research is very significant for companies in the food and beverage sub-sector because it provides guidelines in determining strategies to increase revenue sustainably and operational cost efficiency in increasing corporate profits which has an impact on income tax management.